Engineered Gold-Based Nanomaterials: Morphologies and Functionalities in Biomedical Applications. A Mini Review - Iole Venditti (Bioengineering, 2019)
In the last decade, several engineered gold-based nanomaterials, such as spheres, rods, stars, cubes, hollow particles, and nanocapsules have been widely explored in biomedical fields, in particular in therapy and diagnostics. As well as different shapes and dimensions, these materials may, on their surfaces, have specific functionalizations to improve their capability as sensors or in drug loading and controlled release, and/or particular cell receptors ligands, in order to get a definite targeting. In this review, the up-to-date progress will be illustrated regarding morphologies, sizes and functionalizations, mostly used to obtain an improved performance of nanomaterials in biomedicine. Many suggestions are presented to organize and compare the numerous and heterogeneous experimental data, such as the most important chemical-physical parameters, which guide and control the interaction between the gold surface and biological environment. The purpose of all this is to offer the readers an overview of the most noteworthy progress and challenges in this research field.